IMPLEMENTATION OF TASIKMALAYA MAYOR REGULATION NO. 18 YEAR 2011 ABOUT AREAS WITHOUT CIGARETTES IN THE SCHOOL OF THE TASIKMALAYA CITY SCHOOL: Array - Dede Jamaludin; Endah Vestikowati (Faculty of Social And Political Science Universitas Galuh, 2020)
This research is motivated by the absence of written policies and monitoring staff about No-Smoking Areas in schools, the Regional Government has not fully provided guidance in the form of socialization, weak Internal Supervision (Principal) and External Supervision conducted by Regional Apparatus Organizations and the absence of sanctions or reprimands strict to everyone and / or body that violates. The purpose of this study is to uphold discipline and provide understanding to students and those in the school environment about the dangers of smoking to health. The research method used in this research is descriptive qualitative method. Tasikmalaya Mayor Regulation No. 18 of 2011 concerning the No Smoking Area in the Tasikmalaya City School Environment has not been implemented well or was not carried out well. The obstacles faced include the absence of Standard Operating Procedures and strict sanctions, lack of socialization and provision of facilities and infrastructure to support policies in schools, there are still policy implementers who are still smoking and efforts that have been carried out namely the school makes and issues written policies or SOPs and accompanied by strict sanctions, deliver full socialization on a regular basis, increase leadership supervision in the school environment on an ongoing basis.